Deaminative cross-coupling of amines by boryl radical β-scission - Zhenhua Zhang; Giovanni Lonardi; Thomas Sephton; Yusuf C. Guersoy; Chiara Stavagna; Giovanni V. A. Lenardon; Massimo Bietti; Daniele Leonori (Nature, 2025)
Abstract Amines are among the most common functional groups in biologically active molecules and pharmaceuticals 1–3 , yet they are almost universally treated as synthetic end points 4 . Here we report a strategy that repositions native primary, secondary and tertiary amines as handles for cross-coupling. The platform relies on in situ activation through borane coordination and exploits a copper catalytic redox system that generates amine-ligated boryl radicals, which undergo β-scission across the C( sp 3 )–N bond to release alkyl radicals. These intermediates engage in copper-catalysed cross-couplings with a broad range of C-based, N-based, O-based and S-based nucleophiles. The method tolerates diverse amine classes, enables modular functionalization and supports late-stage diversification of complex drug scaffolds. Also, amides can be incorporated into the manifold through reductive funnelling. This work establishes a general approach to deaminative C–N bond functionalization and introduces a distinct approach for making and modifying drug-like molecules.